Solvent-Induced Crystallization Method for High-Performance and Long-Term Stability Flexible Perovskite Photodetectors - Lei, Zhang; Shugang, Li; Tianjun, Zhang; Shuang, Song; Hongyu, Pan (Frontiers in Materials, 2022)
A novel solvent-induced fabrication method is been induced to synthesize perovskite thin film on flexible substrates. The high-quality CH3NH3PbI3 thin film is successfully fabricated, and further application is applied in the stable flexible photodetector. Compared with the reported results, this method achieves a low-temperature and low-cost perovskite thin film fabrication process on flexible substrate. The constructed CH3NH3PbI3 layer possesses advantages of highly crystalline, uniformity and compact in large area. The flexible photodetector based on the as-prepared perovskite thin film exhibits excellent performance and long-term stability. The EQE and R of the flexible PDs reached 8 × 102 % and 3.6 A/W, respectively. At the same time, the flexible PDs showed superior stability and high performance after 15 days continuous working. The presented high-quality perovskite thin film fabrication method and high-performance flexible perovskite PDs are expected to apply in developing novel optoelectronic devices.